Clinical spectrum of pneumonia in children aged 1 month to 18 years by serum polymerase chain reaction, in a tertiary care centre in Bengaluru, Karnataka, India - S., Ramya H.; Gopi, Anjana; Elango, Vivetha; Joseph, Dona (International Journal of Contemporary Pediatrics, 2020)
Background: Pneumonia accounts for 15% all deaths in children under 5 years of age, being the single largest infectious cause of deaths in children worldwide according to WHO. Establishing the exact etiological factor is a difficult task, as there are no definite clinical, radiological markers to differentiate between causative organisms. Hence by detecting the genetic material of causative organism by serum PCR (polymerase chain reaction) and correlating it with the clinical and radiological features can help in appropriate use with antibiotics. Methods: It is a observational study conducted in department of paediatrics KIMS hospital Bangalore, India which included inpatients admitted with clinical and radiological features of pneumonia over a study period from February 2018-April2019 .In this study we excluded immunocompromised children . After obtaining informed written consent, detailed history and clinical examination was done. Investigations including complete hemogram, CXR were done. Under sterile precautions, blood samples for serum PCR and blood culture and sensitivity were obtained. Serum PCR was done for a panel of 33 respiratory pathogens. Results: Etiological agents were identified in 63% of cases. Streptococcus pneumoniae was the most common causartive agent being detected in 50.6% of the cases. Staphylococcus aureus has been detected to be the second common organism 16%. Conclusions: In our study Pneumococci was identified in 50.6% of cases. Multiplex serum PCR could be a useful rapid diagnostic tool to identify the etiological agents. Introduction of pneumococcal vaccine worldwide in government immunization schedule, nationwide will help to reduce the disease burden caused by Streptococcus pneumoniae.